The Two Taríacuris and the Early Colonial and Prehispanic Past of Michoacán - Haskell, David L. (David Louis) (Book collections on Project MUSE., 2018)
"Investigates how elites of the Tarascan kingdom of Central Mexico sought to influence interactions with Spanish colonialism by reworking the past. Examines the rhetorical power of the Relación de Michoacán--by Franciscan friar Jerónimo de Alcalá and explaining the structure of the narrative, not just its content"--Provided by publisher.